Segregation of boron at prior austenite grain boundaries in a quenched martensitic steel studied by atom probe tomography. (February 2015) - Li, Y.J.; Ponge, D.; Choi, P.; Raabe, D.
Abstract : The distribution of B and other alloying elements (C, Cr, Mo) at prior austenite grain boundaries (PAGBs) and in the matrix was quantified by atom probe tomography in a quenched martensitic steel. B and Mo were observed to be segregated only at PAGBs and to be absent at martensite–martensite boundaries. C is segregated both at PAGBs and at martensite–martensite boundaries, whereas Cr is homogeneously distributed in the probed volume. Our results indicate that B undergoes a non-equilibrium segregation.